Behavioural patterns of two native Leiopelma frogs and implications for their conservation - Ramirez Saavedra, Patricia Alejandra
Amphibian populations are in general decline internationally. The current situation of amphibian populations highlights the urgent need for comprehensive information on species’ ecology to better assess conservation and management strategies. Movement behaviour and microhabitat selection give insights into how amphibians use the environment and interact with their surroundings, and are essential to establishing their sensitivity to the global decline phenomenon and identifying the critical habitat features essential for their success. New Zealand native frogs (Anura: Leiopelmatidae, Leiopelma, nine species) were formerly distributed throughout New Zealand, but habitat modification and predation by introduced mammalian predators have influenced recent (Holocene) extinctions and declines, reducing the fauna to four species with major range reductions. All extant Leiopelma are classified as threatened both nationally and internationally, creating an urgent need for species-specific behavioural research to support conservation management. I investigated activity, movement behaviour and microhabitat use of L. archeyi and L. pakeka for better evaluation of long term population viability and improved husbandry in captivity. L. archeyi is the smallest of the Leiopelma species and has been able to co-occur with introduced predators (e.g. rats), whereas L. pakeka is the largest, and the only natural population is confined to a predator-free island. I used a fine-scale tracking technique (i.e. non-toxic fluorescent powders) to track L. archeyi and L. pakeka movements throughout their activity periods when on the surface in their natural habitats, Whareorino Forest and Maud Island, respectively, to obtain detailed information on their activity patterns, movement behaviour, and microhabitat and retreat site use. I investigated in more detail L. pakeka retreat sites by measuring the dimensions of the retreat site entrances (width, height and diameter) as well as the activity inside those retreat sites. Lastly, I used long-term frog survey data to examine the indirect impacts (i.e. behavioural changes) ship rats (Rattus rattus) may have on L. archeyi by studying the microhabitat use and home range of this species in an area with and without rat control within Whareorino Forest. L. archeyi had a longer activity period than L. pakeka with the former being active up to two hours after sunrise, but L. pakeka moved more and further than L. archeyi during their activity periods. Additionally, L. archeyi had a smaller home range compared to L. pakeka which suggests more prominent site fidelity and more sedentary behaviour in this species. Both species actively sought out specific microhabitats among the ones that were available, either to use during movement or to use as retreat sites, but those microhabitat types also differed between species. L. archeyi were more often found above ground level than L. pakeka and tended to use microhabitats that provided cover. L. archeyi preferred to use trees as retreat sites (roots, branches or trunk) whereas L. pakeka used trees (roots) and rocks. L. pakeka retreat sites had lower and more stable temperatures than outside retreats. Frogs were active inside retreats with no evidence of sleep behaviour for at least the first few hours of retreat use. In the rat control area, L. archeyi used more soil, leaf litter and ferns, and were also more likely to be found at ground level than frogs in the presence of higher numbers of rats. Abiotic factors also influenced movement patterns and microhabitat selection of both species, affirming water balance and thermoregulation are important drivers in frog behaviour. Behavioural attributes and small body size could be aiding in the persistence of L. archeyi in the presence of rats, and large body size and differences in behavioural attributes are likely to put L. pakeka at risk if rats were to reach their habitat. My findings inform on the ecology and behaviour of two Leiopelma species providing valuable information on their habitat requirements, which will enable more effective captive husbandry and better assessment of the appropriateness of translocation sites, aiding in their conservation management. Internacionalmente, las poblaciones de anfibios están en declive. La situación actual de las poblaciones de anfibios resalta la urgente necesidad de más información sobre la ecología de especies para lograr una mejor evaluación de las estrategias de conservación y manejo. Los estudios de movimiento y selección de micro hábitat revelan cómo los anfibios usan el ambiente y cómo interactúan con su entorno, y son esenciales para establecer su sensibilidad al fenómeno global de declive y para identificar estructuras del hábitat que son críticas para su persistencia. Las ranas nativas de Nueva Zelanda (Anura: Leiopelmatidae, Leiopelma, nueve especies) se encontraban previamente distribuidas por toda Nueva Zelanda, pero la modificación del hábitat y la depredación por parte de mamíferos introducidos han influenciado las recientes (Holoceno) reducciones y extinciones de especies, reduciendo la fauna a cuatro especies con considerables reducciones en su rango de distribución. Todas las especies existentes de Leiopelma se encuentran clasificadas como en peligro, tanto nacional como internacionalmente, creando una urgente necesidad de más investigación acerca del comportamiento de estas especies para apoyar el manejo de su conservación. En esta tesis investigué los patrones de actividad, movimiento y uso del micro hábitat por parte de L. archeyi y L. pakeka para una mejor evaluación de su viabilidad poblacional a largo plazo y para mejorar su crianza en cautiverio. L. archeyi es la más pequeña de las especies de Leiopelma y ha sido capaz de coexistir con depredadores introducidos (e.g. ratas), mientras que L. pakeka es la más grande, y la única población natural de esta especie está confinada a una isla libre de depredadores. Utilicé una técnica de seguimiento a nivel de individuo (i.e. polvos fluorescentes no tóxicos) para seguir los movimientos de L. archeyi y L. pakeka durante su período de actividad estando en la superficie en sus hábitats naturales, Whareorino Forest y Maud Island, respectivamente, para obtener información detallada de actividad, movimiento y uso de micro hábitat y refugios. Investigué en más detalle los refugios de L. pakeka mediante la medición de las dimensiones de la entrada del refugio (ancho, alto y diámetro) como también de la actividad de las ranas en su interior. Finalmente, utilicé una base de datos de censos de ranas para examinar los impactos indirectos (i.e. cambios conductuales) que la rata negra (Rattus Rattus) podrían causar en L. archeyi, mediante el estudio del uso del micro hábitat y rango de hogar de esta especie en áreas con y sin control de ratas en Whareorino Forest. L. archeyi presentó un período de actividad más largo que L. pakeka, estando activa hasta dos horas después del amanecer, pero L. pakeka se movió más y más lejos que L. archeyi durante su período de actividad. Adicionalmente, el rango de hogar de L. archeyi fue más pequeño que el de L. pakeka, lo cual sugiere una mayor fidelidad de sitio y sedentarismo en la primera especie. Ambas especies utilizaron micro hábitats específicos dentro de los que se encontraban disponibles en su hábitat, ya sea usándolos durante su movimiento o como refugios, pero estos micro hábitats también difirieron entre ambas especies. L. archeyi se encontró más frecuentemente sobre el nivel del suelo que L. pakeka y tendió a utilizar micro hábitats que proveían de cobertura. L. archeyi prefirió el uso de árboles como refugio (raíces, ramas y tronco), mientras que L. pakeka utilizó árboles (raíces) y rocas. Los refugios de L. pakeka presentaron temperaturas menores y más estables que el ambiente. Los individuos de L. pakeka se encontraron activos dentro de sus refugios, sin evidencia de que éstos duerman por lo menos durante las primeras horas del uso del refugio. En el área con control de ratas, L archeyi utilizó más tierra, hojarasca y helechos, y se encontró más frecuentemente a nivel del suelo que aquellas ranas en la presencia de un mayor número de ratas. Factores abióticos también influenciaron el movimiento y selección de micro hábitat en ambas especies, corroborando que el balance hídrico y la termorregulación son motores importantes en la conducta de estas ranas. Su conducta y pequeño tamaño corporal podrían estar ayudando en la persistencia de L. archeyi en la presencia de ratas, mientras que su mayor tamaño y diferente conducta podrían poner en riesgo a L. pakeka si las ratas llegaran a su hábitat. Mis resultados entregan información respecto a la ecología y conducta de dos especies de Leiopelma, proporcionando información invaluable respecto a sus requerimientos de hábitat, lo cual ayudará a mejorar su crianza en cautiverio y la selección de sitios de translocación apropiados, ayudando en el manejo de su conservación.